2021
DOI: 10.1093/neuros/nyaa580
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiotherapy Versus Watchful Waiting for World Health Organization Grade II Atypical Meningioma: A Single-Institution Experience

Abstract: BACKGROUND Atypical meningiomas (AMs) are meningiomas that have a higher rate of recurrence than grade I meningioma. Due to the higher risk of recurrence, adjuvant radiotherapy (RT) after resection of AM has been employed. At our institution, some neurosurgeons employ adjuvant RT on all primarily resected AMs, while others employ watchful waiting with serial imaging. OBJECTIVE To study the effect of adjuvant RT on newly resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Our study demonstrated significantly improved PFS in patients who received adjuvant RT compared with patients treated with surgery alone (median, 5.9 vs 2.1 years; P = .0017), which is consistent with the results from other series. 7 , 10 , 11 , 17 , 18 , 19 , 20 , 21 , 22 In the largest and most recent of these series, Lee et al reported significantly higher recurrence rates in patients with atypical meningiomas treated with surgery alone compared with surgery and adjuvant RT, with a median time to recurrence of 1.9 versus 4.5 years. 17 Two large studies using data from the National Cancer Database also reported improved OS with adjuvant RT for WHO grade 2 meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated significantly improved PFS in patients who received adjuvant RT compared with patients treated with surgery alone (median, 5.9 vs 2.1 years; P = .0017), which is consistent with the results from other series. 7 , 10 , 11 , 17 , 18 , 19 , 20 , 21 , 22 In the largest and most recent of these series, Lee et al reported significantly higher recurrence rates in patients with atypical meningiomas treated with surgery alone compared with surgery and adjuvant RT, with a median time to recurrence of 1.9 versus 4.5 years. 17 Two large studies using data from the National Cancer Database also reported improved OS with adjuvant RT for WHO grade 2 meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…24 There are multiple prospective, randomized studies aimed to further investigate the role of ART for the postoperative care of patients with AM, regardless of whether or not GTR was achieved. 19 The phase-II Radiation Therapy Oncology Group (0539 trial) recently reported preliminary data that found no significant difference in progression-free survival between patients with AM who received ART and those who did not. 20,21 The European Organization for Research and Treatment of Cancer (22,024) is another observational prospective trial investigating ART for newly resected AM and grade-III meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…1 , 63.7 months) was longer than we observed in previously reported data concerning AMs resected at our institution. 19 It is possible that SBL AMs, owing to their possession of fewer histopathological aggressive features than non-SBL AMs need relatively more time to recur. Therefore, ART may be less effective in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The timing and type of radiation treatment in patients with AM is controversial. A number of studies advocate upfront adjuvant EBRT, [8][9][10] some reports favor post-operative surveillance with salvage radiotherapy especially for those following GTR, [11][12][13]18] while a third group advocate for SRS either as an adjuvant or salvage technique. [15,17,19,20] We found that upfront adjuvant SRS and salvage SRS for late recurrences were equally effective, whereas salvage SRS for early recurrence (7-18 months following resection) was a signi cant risk for tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…[7] External beam radiation therapy (EBRT) is commonly used to reduce the chance of tumor growth after resection for patients with AM, but no consensus has been reached as to whether or not post-operative EBRT is bene cial. [8][9][10][11][12][13][14] Stereotactic radiosurgery (SRS) is also frequently employed for patients with residual or recurrent AM. [15][16][17][18][19][20] These studies are typically comprised of a heterogeneous group of patients including both AM and MM, patients with genetic conditions such as neuro bromatosis or meningiomatosis, and radiation-induced tumors.…”
Section: Introductionmentioning
confidence: 99%